2019
DOI: 10.2217/epi-2018-0136
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Type-Specific DNA Methylation Patterns in Epilepsy: A Discordant Monozygotic Twin Approach

Abstract: Aim: Epilepsy is a common neurological disorder characterized by recurrent seizures. We performed epigenetic analyses between and within 15 monozygotic (MZ) twin pairs discordant for focal or generalized epilepsy. Methods: DNA methylation analysis was performed using Illumina Infinium MethylationEPIC arrays, in blood and buccal samples. Results: Differentially methylated regions between epilepsy types associated with PM20D1 and GFPT2 genes in both tissues. Within MZ discordant twin pairs, differentially methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Finally, it is important to highlight the role of PM20D1 in neurological disorders. In addition to its involvement in AD and PD (as detailed in previous sections), hypermethylation of CpG sites in PM20D1 (and presumably reduced expression) has been associated with an increased risk of suffering chronic postsurgical pain [102] . Additionally, it has been reported that PM20D1 is differentially methylated between different types of epilepsy (focal vs. generalized epilepsy) [103] .…”
Section: Other Phenotypesmentioning
confidence: 90%
“…Finally, it is important to highlight the role of PM20D1 in neurological disorders. In addition to its involvement in AD and PD (as detailed in previous sections), hypermethylation of CpG sites in PM20D1 (and presumably reduced expression) has been associated with an increased risk of suffering chronic postsurgical pain [102] . Additionally, it has been reported that PM20D1 is differentially methylated between different types of epilepsy (focal vs. generalized epilepsy) [103] .…”
Section: Other Phenotypesmentioning
confidence: 90%
“…The proportion of epithelial cells in oral samples estimated from cytology and DNA methylation was tested using Pearson correlation coefficient. To investigate the age effect on epithelial cell content estimated using DNA methylation, the buccal and saliva sample data from this study was analysed along with seven of our other studies, three published (3,10,11) and four unpublished. These cohorts' details included to investigate the age effect on epithelial cell content was described in supplementary method.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous paper, we observed that epithelial cell content of buccal swabs and saliva was lower in adults compared to children (3). To investigate a possible age effect using epithelial cell content estimated using DNA methylation, we combined buccal swab and saliva data from this study with seven of our other Infinium array studies, including three published (3,10,11) and four unpublished (Figure 5, Supplementary Table 2). We found a moderate negative correlation between age and epithelial cell content estimated by DNA methylation (R = -0.72, p <0.0001, 0.59% of epithelial cell content estimated from DNA methylation), with age accounting for 14% of the variation in epithelial cell content.…”
Section: An Age Effect On Epithelial Cell Content In Salivamentioning
confidence: 99%
See 1 more Smart Citation
“…Another important issue worth mentioning is the role of DNAm for diagnostic and prognostic approaches in epilepsy. As an example, the blood of patients with mTLE-HS has shown specific DNAm patterns (Long et al, 2017) and a concordant-twin study detected patterns that enabled distinction between focal and generalized epilepsy (Mohandas et al, 2019). These results suggest that blood-based DNAm could be a potential biomarker for epilepsy and epileptogenesis, paving the way to a more personalized management of people with epilepsy (PWE).…”
Section: Potential Strategies and Challenges Of Anti-epileptogenic In...mentioning
confidence: 92%